Peningkatan Kemampuan Literasi Digital bagi Siswa Kelas 4 dan 5 SDN Tanjakan 3, Kabupaten Tangerang - Roikhan Mochamad Aziz; Muhammad Asyep Syam’aeni; Nisfina Sya’baniyah; Izzah Corrie Fatihah (Jurnal Pengabdian Pada Masyarakat, 2020)
IMPROVEMENT OF DIGITAL LITERACY ABILITY FOR GRADE 4 AND 5 STUDENTS OF SDN TANJAKAN 3, TANGERANG REGENCY. Digital information resources are very abundant, due to advances in information technology and the internet. The current condition of students in Indonesia, which is a digital native generation, has a high dependence on information retrieval on the internet. Aside from the internet having a positive impact, the internet also has a negative side and that information can spread quickly on the internet. Digital literacy is needed to teach children the basics of socializing and digital security so they can explore the digital world safely and confidently. The subjects of this study were elementary school students in Tanjakan Village, Rajeg, Tangerang. This study uses a practical pragmatic theoretical approach that directs children to learn in groups and together solve each problem. The result of this service program is that digital literacy is carried out according to the desired target, and participants gain insight into information and communication technology and the use of the internet in a healthy and safe manner. With the right internet training, it is expected to avoid the dangers of the internet from the negative side. Participants already know tips on how to find a true or fake news on an internet website, and can surf safely and healthily. Based on the evaluation, participants of SDN Tanjakan 3 understood the material that had been delivered and agreed to use a healthy and safe internet.